2007
DOI: 10.1242/jeb.009555
|View full text |Cite
|
Sign up to set email alerts
|

Lung ventilation contributes to vertical lymph movement in anurans

Abstract: SUMMARY Anurans (frogs and toads) generate lymphatic fluid at 10 times the rate in mammals, largely as a consequence of their very `leaky' vasculature and high interstitial compliance. Lymph is ultimately pumped into the venous system by paired, dorsally located lymph hearts. At present, it is unclear how lymphatic fluid that accumulates in central body subcutaneous lymph sacs is moved to the anterior and posterior lymph hearts in the axillary regions and how lymph is moved, against gravity, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Our description of lymphatic sac-related skeletal muscles and pressure and EMG data support our hypothesis that vertical transport of lymph must be principally accomplished by contraction of skeletal muscles rather than a compliance pump (Hillman et al, 2004;Hillman et al, 2005) or by negative pressures created by the lymph hearts alone (Toews and Wentzell, 1995). Lymphatic movement is also influenced by ventilatory events driven by skeletal muscles (Hedrick et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our description of lymphatic sac-related skeletal muscles and pressure and EMG data support our hypothesis that vertical transport of lymph must be principally accomplished by contraction of skeletal muscles rather than a compliance pump (Hillman et al, 2004;Hillman et al, 2005) or by negative pressures created by the lymph hearts alone (Toews and Wentzell, 1995). Lymphatic movement is also influenced by ventilatory events driven by skeletal muscles (Hedrick et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…Hedrick et al have demonstrated that lung inflation forces lymph in the lateral, ventral and subvertebral lymph sacs anteriorly and posteriorly to the vicinity of the dorsal lymph hearts dorsally and to the axillae of the fore and hindlimbs ventrally (Hedrick et al, 2007). Here, we are concerned with the vertical movement of lymph pooling in sacs in the posterior ventral and inguinal regions of the frog up to the vicinity of the lymph hearts.…”
Section: Introductionmentioning
confidence: 94%
“…Even in the face of high water loss, the skin remains important for cutaneous CO 2 excretion (Boutilier et al, 1979;Burggren and Vitalis, 2005). During anoxia, breathing rate has been shown to progressively decrease until it eventually ceases in Rana pipiens and as lymph movement is dependent on lung ventilation in frogs, the physiological responses to anoxia may inadvertently lower immunity (Winmill et al, 2005;Hedrick et al, 2007) as the lymphatics, as well as the blood, carry immune cells. With a decreased internal immune function, the protection of the skin by AMPs may become increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lymph heart destruction results in a marked increase in red cell volume, interstitial edema and also death (Zwemer and Foglia, 1943;Baustian, 1988). Generated extravascular fluid in anuran amphibians returns to the cardiovascular system through a combination of changes in pressure and volume of the lymph sacs that is driven by effectors such as lung ventilation (inflation and deflation) and skeletal muscle contraction Hedrick et al, 2007). Therefore, from an evolutionary perspective, ventilatory responses that may be modulated by baroreceptor loading and unloading in R. schneideri can contribute to our understanding of a number of pieces of evidence for the influence of the cardiovascular system on the respiratory system in mammals (Brunner et al, 1982;Walker and Jennings, 1998;Baekey et al, 2010;McMullan and Pilowsky, 2010;Stewart et al, 2011).…”
Section: Blood Pressure Homeostasis In Anuran Amphibiansmentioning
confidence: 99%
“…Based on the roles played by lung ventilation in blood volume homeostasis in anurans (Crossley and Hillman, 1999;Hedrick et al, 2007;Hillman et al, 2010Hillman et al, , 2013 and in O 2 delivery to match metabolic demands, we tested the hypothesis that pulmonary ventilation contributes to the baroreflex responses to blood pressure imbalances in R. schneideri, and that this effect is modulated by changes in temperature. To this end, baroreflex function was assessed through pharmacological interventions on arterial blood pressure, i.e.…”
Section: Introductionmentioning
confidence: 99%